APPLICATION OF AUGMENTED REALITY THROUGH A SCIENTIFIC APPROACH TO STUDENTS' CRITICAL THINKING ABILITY - Lilis Lismaya; Agus Priyanto; Putri Ayu (Indonesian Journal of Learning and Instruction, 2022)
This research is motivated by the lack of learning media that can facilitate students' critical thinking skills in learning during the covid-19 pandemic. Critical thinking ability is a very important competency to be developed through a scientific approach. This ability is indispensable in everyday life. The purpose of this study was to analyze the effect of students' critical thinking skills through the application of Augmented Reality through a scientific approach. The method used in this research is Quasi Experimental with pretest-posttest control group design. The population in this study were students of class XI science at SMA Negeri 1 Cigugur which consisted of 3 science classes with a total of 78 students. The samples used in this study were two classes, namely class XI IPA 1 and XI IPA 3. The sampling technique used was purposive sampling. The instruments used are description tests, observation sheets and student response questionnaires to the application of augmented reality through a scientific approach. Based on the results of analysis and calculations with hypothesis testing, the results obtained are H1 is accepted and Ho is rejected, meaning that there is an increase in students' critical thinking skills by applying Augmented Reality through a scientific approach.Keywords: Augmented Reality; scientific approach; critical thinking.